A Multi-Dimensional Perspective on Service Innovation in the IT Services Industry - Ghoshal, Sankar; Roy, Rahul; Dutta, Apurba Kishore (Journal of Strategic Innovation and Sustainability, 2018)
Innovation in service manifests itself in multiple dimensions - a change in the service offering or changes in any of the organizational processes delivering that service. Service firms need to demonstrate a variety of dynamic capabilities to design new services and deliver them. An exploratory case study, based on a major innovation in an IT service engagement, is used to bring out the multiple dimensions of service innovation. Further, it brings out the role played by dynamic capabilities in realizing that innovation. This implies that service firms would require flexibility in the delivery mechanism, to be able to innovate successfully.